Adjustable Lateral-Titling Mechatronic Bed for Assisting Pediatric Posture Drainage - Srilomsak, Sapon; Anuwatpanich, Khunakon; Tubglam, Supawadee; Prempraneerach, Pradya (International Journal of Industrial Engineering: Theory, Applications and Practice, 2024)
Lower respiratory tract infections (LRTIs) are commonly found among infants and result in high mortality. Airway clearance techniques (ACTs) like postural drainage (PD) help clear pulmonary secretions in the lungs. A mechatronic bed was designed and developed using two symmetrical four-bar linkage mechanisms for the lateral tilting of a pediatric patient while keeping both side rails in a vertical position for safe operation. This assists in performing PD. The mechatronic bed allows a single caretaker to manually perform PD adjustment through a Raspberry Pi graphical user interface (GUI), thereby controlling the bed’s lateral tilt angle between [-25°, 25°] using a geared DC servo-motor. Validation with a 3.4-kg infant simulator confirmed safety. No rolling or flipping motion of the infant simulator was observed, with only minor slippage at extreme angles. This bed structure and electronic equipment comply with medical device safety guidelines, ensuring the safety of pediatric patients and caregivers. The mechatronic bed significantly enhances PD treatment safety and efficiency, reducing caregiver strain and improving patient recovery in pediatric care.